Percutaneous afferent lymphatic vessel sclerotherapy for postoperative lymphatic leakage after previous ineffective therapeutic transpedal lymphangiography - F. Pan; M. Loos; T. D. Do; G. M. Richter; H. U. Kauczor; T. Hackert; C. M. Sommer (European Radiology Experimental, 2020)
Abstract Background To demonstrate the efficacy of percutaneous computed tomography (CT)-guided afferent lymphatic vessel sclerotherapy (ALVS) in the treatment of postoperative lymphatic leakage (LL) after ineffective therapeutic transpedal lymphangiography (TL). Methods A retrospective review in this institute involving 201 patients was conducted from May 2011 to September 2018. Patients diagnosed with postoperative LL undergoing ineffective therapeutical TL before the performance of percutaneous CT-guided ALVS were involved. Technical success and clinical success of TL and ALVS were established. The technical success and efficacy of ALVS in the treatment of postoperative LL after ineffective therapeutic TL were assessed. The clinical success rate of ALVS is also assessed, and the complications are reviewed. Results In total, nine patients were involved including three patients (33.3%) presented with chylothorax, three patients (33.3%) presented with inguinal lymphatic fistula/lymphocele, and three patients (33.3%) presented with lymphatic fistula in the thigh; 27 ± 18 days (mean ± standard deviation) after surgery, therapeutic TL was successfully performed and showed definite afferent lymphatic vessel and leakage site in all the patients. Due to clinical failure after TLs, the following ALVS was performed with a mean interval of 12 ± 8 days after TL. The technical success rate was 9/9 (100.0%, 95% confidence interval [CI] 63.1–100.0%). An average of 2.7 ± 1.3 mL 95% ethanol as sclerosant agent was injected during the procedure. The clinical success was observed in 8 of the 9 patients (88.9%, 95% CI 51.8–99.7%) with a time between ALVS and the LL cure of 8 ± 6 days. No complications were reported. Conclusions Our results showed the role of percutaneous CT-guided ALVS as a safe, feasible, and effective salvage treatment for postoperative LL after ineffective TL.